Perpetuating Racism in the Field of Adult Education: A Process of Liberation for White European Decent Professors - Carole L. Lund (Adult Education Research Conference, 2007)
The purpose of this case study research was to identify attitudes and analyze the behaviors of white European descent members of the adult education professoriate to determine how and in what ways they perpetuate racism. This research may change the way white European descent adult educators interact with colleagues and students of color.